Pelvic floor muscle training vs. Pilates exercises on the sexual function of post-menopause women with urinary incontinence: PFMT vs. Pilates on the sexual function - Gonzaga, Sabrina; Oliveira, Raphael Gonçalves de; Paiva, Bárbara Rebeca Matos; Domanoski, Natália Barbosa; Dutra, Letícia Lussi; Oliveira, Laís Campos de (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: A significant percentage of postmenopausal women suffer from urinary incontinence (UI), which can impair sexual function. Pelvic floor muscle training (PFMT) is the main treatment to improve UI, and it can also be used to improve sexual function. On the other hand, other forms of intervention, such as Pilates exercises, which require activation of the pelvic floor muscles, have been suggested as a possible adjuvant in UI-related outcomes. Objectives:To verify the effective-ness of PFMT vs. Pilates on sexual function in postmenopausal women with UI. Methods:40 postmenopausal women with UI were randomized into two groups: PFMT (n = 20) and Pilates (n = 20). Interventions in both groups were performed for 12 weeks, three timesa week, for 30 minutes. Sexual function was assessed using the Female Sexual Function Index (FSFI) questionnaire. Mann-Whitney and Wilcoxon U tests were used for inter and intragroup comparisons, respective-ly. Results:There was no difference in the intergroup comparison, for any FSFI domain (p > 0.05). There was a significant intragroup difference, in both groups, in the desire, lubrication and total score domains, with effect sizes ranging from small to large. There were also significant intragroup results for the orgasm and pain domains in the PFMT group, with a small effect size. Conclusion:There was no evidence that PFMT is different from Pilates in the sexual function of postmenopau-sal women with UI, therefore, the choice between PFMT or Pilates may be based on preferences and costs for the patient or health professional.